Focal Adhesion Kinase as a RhoA-activable Signaling Scaffold Mediating Akt Activation and Cardiomyocyte Protection - Del Re, Dominic P. (American Society for Biochemistry and Molecular Biology, 2008)
RhoA a small G-protein that has an established role in cell growth and in regulation of the actin cytoskeleton. Far less is known about whether RhoA can modulate cell fate. We previously reported that sustained RhoA activation induces cardiomyocyte apoptosis (Del Re, D. P., Miyamoto, S., and Brown, J. H. (2007) J. Biol. Chem. 282, 8069–8078). Here we demonstrate that less chronic RhoA activation affords a survival advantage, protecting cardiomyocytes from apoptotic insult induced by either hydrogen peroxide treatment or glucose deprivation. Under conditions where RhoA is protective, we observe Rho kinase-dependent cytoskeletal rearrangement and activation of focal adhesion kinase (FAK). Activation of endogenous cardiomyocyte FAK leads to its increased association with the p85 regulatory subunit of phosphatidylinositol-3-kinase (PI3K) and to concomitant activation of Akt. Treatment of isolated perfused hearts with sphingosine 1-phosphate recapitulates this response. The pathway by which RhoA mediates cardiomyocyte Akt activation is demonstrated to require Rho kinase, FAK and PI3K, but not Src, based on studies with pharmacological inhibitors (Y-27632, LY294002, PF271 and PP2) and inhibitory protein expression (FAK-related nonkinase). Inhibition of RhoA-mediated Akt activation at any of these steps, including inhibition of FAK, prevents RhoA from protecting cardiomyocytes against apoptotic insult. We further demonstrate that stretch of cardiomyocytes, which activates endogenous RhoA, induces the aforementioned signaling pathway, providing a physiologic context in which RhoA-mediated FAK phosphorylation can activate PI3K and Akt. We suggest that RhoA-mediated effects on the cardiomyocyte cytoskeleton provide a novel mechanism for protection from apoptosis.